Der Arbeitsmarkt erlebt derzeit eine Zeitenwende; The labor market is currently experiencing a turn of eras - Wido Geis-Thöne (Wirtschaftsdienst, 2022)
– Increasing labour shortages are mainly due to demographic developments - specifically the baby boom in Germany, with a strong peak in the early 1960s. Despite strong immigration in recent years, the ratio of 20-24 year-olds to 60-64 year-olds was only 75 to 100 in 2021, and if younger cohorts are taken into account, it was even less favourable. This demographic gap can only be closed by migration. However, the workers coming into the country should have qualifications that are compatible with the German labour market, which severely limits the group of potential immigrants. Therefore, previously inactive population groups must also be attracted to gainful employment and automation must be promoted.
Keywords: J11; J21; F22; 330; Arbeitsmarkt; Alternde Bevölkerung; Arbeitsmigranten; Deutschland